Global Perspectives on Orhan Pamuk
XVIII, 206 p.
Keywords: Explores existential and political themes in Orhan Pamuk's work and investigates the apparent contradictions in an arena where Islam and democracy are often seen as opposing and irreconcilable terms. Existential themes delve into literary nuances in Pamuk that discuss love, happiness, suffering, memory and death.